2011
DOI: 10.1089/jmf.2010.0200
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antimicrobial Activity of Sorrel (Hibiscus sabdariffa) onEsherichia coliO157:H7 Isolated from Food, Veterinary, and Clinical Samples

Abstract: The use of medicinal plants as natural antimicrobial agents is gaining popularity. Sorrel (Hibiscus sabdariffa) is widely used for the treatment of diseases. The objective of this study was to investigate the antimicrobial activity of sorrel on Escherichia coli O157:H7 isolates from food, veterinary, and clinical samples. Phenolics of the calyces were extracted from 10 g of ground, freeze-dried samples using 100 mL of 80% aqueous methanol. Concentrations of 10%, 5%, and 2.5% methanol extract of sorrel were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 37 publications
2
58
0
1
Order By: Relevance
“…The antimicrobial activity of H. sabdariffa has been reported against foodborne and food spoilage microorganisms, like E. coli O157:H7, is a major foodborne pathogen [23,37], also against Gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumonia, Proteus vulgaris, Salmonella enterica and some multidrug resistant Salmonella strains, in addition to some Gram-positive bacteria such as Bacillus subtilis, S. aureus, Staphylococcus epidermis, and Staphylococcus cereus [24,25,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial activity of H. sabdariffa has been reported against foodborne and food spoilage microorganisms, like E. coli O157:H7, is a major foodborne pathogen [23,37], also against Gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumonia, Proteus vulgaris, Salmonella enterica and some multidrug resistant Salmonella strains, in addition to some Gram-positive bacteria such as Bacillus subtilis, S. aureus, Staphylococcus epidermis, and Staphylococcus cereus [24,25,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Finely powdered and extracted in a Soxhlet with 2 L of methanol for 48 h. The methanol was evaporated by vacuum pressure, the ×10 concentrated extract 10 mg/ml was used in further experiments [23,25,31].…”
Section: Plant Materials and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is performed by activating fibroblast that has similar properties to smooth muscle cells, enabling necessary contraction and tension for damage repair. Growth factors are of great importance in the migration, proliferation, and differentiation of epithelial cells as well as in the formation of connective tissue and the growth of new vessels during the healing process [2,16,19].…”
Section: Sarwono and Suniartimentioning
confidence: 99%
“…Former studies also reported that surgical wounds developed keloid tissue (collagen scarring) or led to extended coagulation necrosis in all tissue layers of the oral cavity [6,14,19]. Former in vitro study reported that roselle extract showed the novel property as potential supplement and gene protectant against oxidative damage to culture hematopoietic stem cells.…”
Section: Sarwono and Suniartimentioning
confidence: 99%